Avaliação histopatológica de tecidos de hamsters (Mesocricetus auratus) experimentalmente infectados com estirpes de Leptospira spp. de sorogrupos diferentes - Pinto, P. S.; Barbosa, C.; Barbosa, J. M. S.; Ferreira, A. M. R.; Lilenbaum, W. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is an infectious disease determined by the different serogroups of Leptospira spp. that affects several animal species, including humans. Studies with experimental infection are essential for understanding the transmission, colonization and pathogenesis of leptospirosis. Some studies demonstrated differences in Leptospira spp. infection by varying the inoculation route, the inoculum dose and the inoculated strain, but few have evaluated the particularities of infection by strains of different serogroups in the same study that was performed in the present study.